Give Greece a chance - Michael Mitsopoulos; Theodore Pelagidis (Intereconomics, 2015)
The current complicated economic situation in Greece - and the rising political uncertainty that once again accompanies it - has important repercussions for growth, incomes, employment and the banking system in both the short and long term. The new Greek government is trying to perform a balancing act that will on the one hand satisfy its electorate and the more extreme fractions within the Syriza party and on the other hand offer a number of key concessions to the country's European partners. It is thus imperative to carefully select which concessions the EU should make towards the new government.
Keywords: 330; Wirtschaftskrise; Länderrisiko; Griechenland